Opening access – views from the South - Browse, Lucy; Cumming, Sioux; Murray, Susan (Technical Centre for Agricultural and Rural Cooperation, 2013)
Initiatives in Africa to open up access to research results are helping countries there face development challenges and bridge the knowledge gap with industrialised countries